Vitrified-warmed embryo transfer is associated with mean higher singleton birth weight compared to fresh embryo transfer. (August 2016) - Beyer, Daniel Alexander; Griesinger, Georg
Abstract: Objective: To test for differences in birth weight between singletons born after IVF with fresh embryo transfer vs. vitrified-warmed 2PN embryo transfer (vitrification protocol). Design: Retrospective analysis of 464 singleton live births after IVF or ICSI during a 12 year period. Setting: University hospital. Interventions: Fresh embryo transfer, vitrified-warmed 2PN embryo transfer (vitrification protocol). Main outcome measures: Birth weight standardized as a z -score, adjusting for gestational week at delivery and fetal sex. As a reference, birth weight means from regular deliveries from the same hospital were used. Multivariate regression analysis was used to investigate the relationship between the dependent variable z -score (fetal birth weight) and the independent predictor variables maternal age, weight, height, body mass index, RDS prophylaxis, transfer protocol, number of embryos transferred, indication for IVF treatment and sperm quality. Results: The mean z -score was significantly lower after fresh transfer (−0.11 ± 92) as compared to vitrification transfer (0.72 ± 83) ( p  < 0.001). Multivariate regression analysis indicated that only maternal height and maternal body mass index, but not type of cryopreservation protocol, was a significant predictor of birth weight. Conclusions: In this analysis focusing on 2PN oocytes, vitrified-warmed embryo transfer is associated with mean higher birth weight compared to fresh embryo transfer. Maternal height and body mass index are significant confounders of fetal birth weight and need to be taken into account when studying birth weight differences between ART protocols.